High-strength low-stress continuous SiC fiber reinforced Ti3Al composite material as well as preparation method and application thereof

By introducing the Mo layer and alternately deposition of the Ti3Al/Nb layer at the SiC/Ti3Al composite interface, the problems of mismatch in the thermal expansion coefficient and residual stress in the composite material are solved, and the strength and toughness of the material are significantly improved.

CN119640163AActive Publication Date: 2025-03-18JILIN UNIVERSITY

Patent Information

Application Number
CN202411844347.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-16
Publication Date
2025-03-18
Estimated Expiration
2044-12-16

AI Technical Summary

Technical Problem

During the preparation process, SiCf/Ti3Al composite material faces problems with mismatch in thermal expansion coefficient and residual stress during processing and forming, resulting in material failure.

Method used

Using the method of introducing a Mo layer at the interface of SiC/Ti3Al composite materials, the Mo interface layer is deposited by magnetron sputtering technology, and the Ti3Al layer and Nb layer are alternately deposited to construct a pioneer wire of a multi-layer structure, and then thermal isostatic molding is performed.

Benefits of technology

It effectively enhances the interface strength, reduces the interface residual stress, improves the tensile strength and toughness of the material, and avoids material failure caused by stress concentration.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119640163A_ABST
    Figure CN119640163A_ABST
Patent Text Reader

Abstract

The invention provides a high-strength low-stress continuous SiC fiber reinforced Ti3Al composite material as well as a preparation method and application thereof, and belongs to the technical field of aeronautical materials. The Mo interface layer with the thermal expansion coefficient matched with that of SiC and Ti3Al is introduced to the interface of the SiC / Ti3Al composite material, so that the stable transition of the thermal expansion coefficient is realized, the interface stress is dispersed, the interface bonding strength is further improved, and the stability of the material performance is guaranteed; meanwhile, an Nb element is introduced into a Ti3Al matrix to refine Ti3Al grains and optimize a microstructure, so that the strength and toughness of the material are enhanced, and a Ti3Al / Nb composite structure is constructed to relieve stress concentration and improve the tensile strength, so that the material failure is effectively prevented.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of aviation materials, and specifically relates to a high-strength and low-stress continuous SiC fiber reinforced Ti3Al composite material and a preparation method and application thereof. Background Art

[0002] SiC f / Ti-based composite materials stand out from traditional materials with their light weight, high strength, high rigidity and excellent high temperature resistance, and have become the preferred material in the aerospace field. However, with the continuous advancement of aerospace technology, the thermal environment faced by hot end components is becoming increasingly harsh, which puts higher requirements on the adaptability of materials.

[0003] Ti3Al plays a key role in improving the overall performance of composite materials due to its outstanding properties, such as low density, high strength, good thermal stability and excellent oxidation resistance. It is regarded as an ideal matrix material for composite materials, especially in application scenarios that require both lightweight and high strength. However, SiC f / Ti3Al composites face two problems during the preparation process: on the one hand, the mismatch in thermal expansion coefficients between Ti3Al and SiC fibers has become an important factor restricting its further application. This mismatch may lead to interfacial stress concentration during the preparation and use of the composite material, which in turn causes material failure; on the other hand, when Ti3Al is processed and formed, residual stress is easily generated inside the material due to uneven temperature field distribution and deformation. These residual stresses may be superimposed on external stresses during the service life of the material, causing local stress concentration, promoting crack initiation and expansion, and thus reducing the fracture toughness of the material. Summary of the invention

[0004] The purpose of the present invention is to provide a high-strength and low-stress continuous SiC fiber reinforced Ti3Al composite material and a preparation method and application thereof. The high-strength and low-stress continuous SiC fiber reinforced Ti3Al composite material prepared by the present invention has high strength, low stress and good stability, and can effectively avoid material failure caused by stress concentration and other problems during service.

[0005] In order to achieve the purpose of the present invention, the present invention provides the following technical solutions:

[0006] A method for preparing a high-strength and low-stress continuous SiC fiber reinforced Ti3Al composite material comprises the following steps:

[0007] (1) ion cleaning the SiC fiber containing the carbon layer under argon conditions to obtain a pretreated SiC fiber;

[0008] (2) using Mo as a target material, magnetron sputtering the pretreated SiC fiber under argon conditions to obtain a SiC fiber with a Mo interface layer deposited;

[0009] (3) using a Ti3Al alloy target and Nb as target materials, magnetron sputtering the SiC fiber deposited with the Mo interface layer under argon conditions, and alternately depositing Ti3Al layers and Nb layers on the surface of the SiC fiber deposited with the Mo interface layer to obtain a precursor wire with a multilayer structure;

[0010] The precursor wires with a multi-layer structure are evenly arranged and hot isostatically pressed to obtain the high-strength and low-stress continuous SiC fiber reinforced Ti3Al composite material.

[0011] Preferably, the ion cleaning is carried out in a coating chamber of a magnetron sputtering system, and the vacuum degree in the coating chamber is less than 4×10 -4 Pa; the gas flow value of argon is 40-80 sccm, the ion source voltage is 750-850 V, and the cleaning time is 20-30 min.

[0012] Preferably, the conditions for magnetron sputtering in step (2) include: an argon gas flow rate of 40 to 100 sccm; a vacuum degree in the coating chamber of less than 4×10 -4 Pa, the gas pressure in the coating chamber is 0.7~1.2Pa; the sputtering bias is -40~-150V, the sputtering current is 0.8~1.2A, the power is 300~800W, and the deposition rate is 0.4~1.5μm / h.

[0013] Preferably, the conditions for magnetron sputtering the target in step (3) include:

[0014] When depositing the Ti3Al layer, the argon flow rate is 40-100 sccm and the vacuum degree in the coating chamber is less than 4×10 -4 Pa, the gas pressure in the coating chamber is 0.7~1.2Pa, the sputtering bias is -40~-150V, the sputtering current is 1.6~2.4A, the power is 600~800W, and the deposition rate is 2~4μm / h;

[0015] When depositing the Nb layer, the argon flow rate is 40-100 sccm and the vacuum degree in the coating chamber is less than 4×10 -4 Pa, the gas pressure in the coating chamber is 0.7~1.2Pa, the sputtering bias is -40~-150V, the sputtering current is 0.8~1.2A, the power is 300~500W, and the deposition rate is 0.4~1.5μm / h.

[0016] Preferably, the SiC fiber is a SiC fiber containing a tungsten core; the diameter of the SiC fiber is 90 to 110 μm, and the thickness of the carbon layer is 2 to 4 μm;

[0017] The thickness of the Mo interface layer is 0.5-4 μm.

[0018] Preferably, in step (3), one Ti3Al layer and one Nb layer constitute one period, and the repetition period of the Ti3Al layer and the Nb layer is ≥3;

[0019] The thickness of the single Ti3Al layer is 2 to 6 μm, and the thickness of the single Nb layer is 0.5 to 4 μm.

[0020] Preferably, in the precursor yarn having a multi-layer structure, the total thickness of the SiC fiber surface film layer is 20 to 35 μm.

[0021] Preferably, the hot isostatic pressing is performed at a temperature of 920 to 980° C., a pressure of 120 to 180 MPa, and a time of 1 to 3 hours.

[0022] The present invention also provides a high-strength and low-stress continuous SiC fiber reinforced Ti3Al composite material prepared by the preparation method described in the above technical scheme, which is obtained by hot isostatic pressing of a pioneer wire with a multi-layer structure, and is characterized in that a single pioneer wire with a multi-layer structure includes SiC fibers, carbon layers, Mo interface layers, and alternating Ti3Al layers and Nb layers from the inside to the outside, and the outermost layer of the pioneer wire with a multi-layer structure is a Nb layer.

[0023] The present invention also provides the application of the high-strength and low-stress continuous SiC fiber reinforced Ti3Al composite material described in the above technical solution as an aerospace material.

[0024] The present invention provides a method for preparing a high-strength and low-stress continuous SiC fiber reinforced Ti3Al composite material, comprising the following steps: (1) ion cleaning SiC fiber under argon conditions to obtain pretreated SiC fiber; (2) using Mo as a target material, magnetron sputtering the pretreated SiC fiber under argon conditions to obtain SiC fiber with a deposited Mo interface layer; (3) using Ti3Al alloy target material and Nb as target materials, magnetron sputtering the SiC fiber with the deposited Mo interface layer under argon conditions, alternately depositing Ti3Al layers and Nb layers on the surface of the SiC fiber with the deposited Mo interface layer to obtain a precursor wire with a multilayer structure; uniformly arranging the precursor wire with the multilayer structure, performing hot isostatic pressing to obtain the high-strength and low-stress continuous SiC fiber reinforced TiAl composite material. The present invention adopts a method of introducing a Mo layer at the interface of the SiC / Ti3Al composite material, aiming to enhance the interface strength and reduce the interface residual stress. In view of the difference in thermal expansion coefficients between SiC and Ti3Al, interfacial thermal stress may be induced during the high-temperature molding stage, thus posing a potential threat to the comprehensive performance of the composite material. Mo, with its unique physical properties, has a thermal expansion coefficient that is more compatible with SiC and Ti3Al, and can achieve a smooth transition of the thermal expansion coefficient at the interface of the composite material. It can not only effectively disperse and relieve stress at the interface, but also significantly improve the interfacial bonding strength between SiC and Ti3Al, thereby ensuring that the composite material can maintain its performance stability when experiencing temperature changes.

[0025] At the same time, the present invention introduces Nb elements into SiC / Ti3Al materials to refine Ti3Al grains and optimize their microstructure, thereby improving the strength and toughness of the material. In addition, constructing a Ti3Al / Nb composite structure can effectively alleviate stress concentration, so that the tensile strength of the SiC / Ti3Al composite material is significantly improved while avoiding material failure caused by residual stress accumulation. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0027] Figure 1 The present invention is a preparation flow chart of the high-strength and low-stress continuous SiC fiber reinforced Ti3Al composite material;

[0028] Figure 2 The SiC obtained in Example 1 fCross-sectional SEM images of / C / Mo / (Ti3Al / Nb)9 composite materials; (a) and (b) are cross-sectional SEM images at scales of 100 μm and 30 μm, respectively;

[0029] Figure 3 This is a comparison chart of the tensile strength of the composite materials obtained in Example 1, Comparative Example 1 and Comparative Example 2;

[0030] Figure 4 This is a comparison chart of the residual stress of the composite materials obtained in Example 1, Comparative Example 1 and Comparative Example 2. DETAILED DESCRIPTION

[0031] A method for preparing a high-strength and low-stress continuous SiC fiber reinforced Ti3Al composite material comprises the following steps:

[0032] (1) ion cleaning the SiC fiber containing the carbon layer under argon conditions to obtain a pretreated SiC fiber;

[0033] (2) using Mo as a target material, magnetron sputtering the pretreated SiC fiber under argon conditions to obtain a SiC fiber with a Mo interface layer deposited;

[0034] (3) using a Ti3Al alloy target and Nb as target materials, magnetron sputtering the SiC fiber deposited with the Mo interface layer under argon conditions, and alternately depositing Ti3Al layers and Nb layers on the surface of the SiC fiber deposited with the Mo interface layer to obtain a precursor wire with a multilayer structure;

[0035] The precursor wires with a multi-layer structure are evenly arranged and hot isostatically pressed to obtain the high-strength and low-stress continuous SiC fiber reinforced Ti3Al composite material.

[0036] In the present invention, unless otherwise specified, all preparation raw materials are preferably commercially available products well known to those skilled in the art.

[0037] The present invention performs ion cleaning on SiC fiber containing a carbon layer under argon conditions to obtain pretreated SiC fiber. In the present invention, the SiC fiber is a SiC fiber containing a tungsten core, the diameter of the tungsten core is 10 to 20 μm, in a specific embodiment, it can be 15 μm or 18 μm; the diameter of the SiC fiber is 90 to 110 μm, in a specific embodiment, it can be 95 μm or 100 μm; the thickness of the carbon layer is 2 to 4 μm, in a specific embodiment, it can be 3 μm or 3.5 μm. The present invention has no special requirements on the source of SiC fiber, and commercially available SiC fiber containing a carbon coating or self-prepared can be used.

[0038] In the present invention, the ion cleaning is carried out in the coating chamber of the magnetron sputtering system, and the vacuum degree in the coating chamber is less than 4×10-4 Pa; the gas flow value of argon is 40-80sccm, in a specific embodiment, it can be 50sccm, 60sccm or 70sccm; the ion source voltage is 750-850V, in a specific embodiment, it can be 800V or 820V; the cleaning time is 20-30min, in a specific embodiment, it can be 25min.

[0039] After obtaining the pretreated SiC fiber, the present invention uses Mo as a target material and performs magnetron sputtering on the pretreated SiC fiber under argon conditions to obtain SiC fiber with a Mo interface layer deposited. In the present invention, the conditions for magnetron sputtering in step (2) include: an argon gas flow rate of 40 to 100 sccm, and in a specific embodiment, it can be 50 sccm, 60 sccm or 80 sccm; the vacuum degree in the coating chamber is less than 4×10 -4 Pa, the gas pressure in the coating chamber is 0.7-1.2Pa, and in a specific embodiment, it can be 0.8Pa or 1.0Pa; the sputtering bias is -40--150V, and in a specific embodiment, it can be -80V, -100V or -130V; the sputtering current is 0.8-1.2A, and in a specific embodiment, it can be 1.0A; the power is 300-800W, and in a specific embodiment, it can be 350W, 400W, 550W or 750W; the deposition rate is 0.4-1.5μm / h, and in a specific embodiment, it can be 0.8μm / h or 1.2μm / h.

[0040] In the present invention, the thickness of the Mo interface layer is 0.5 to 4 μm, and in a specific embodiment, it can be 1 μm, 2 μm or 3 μm. The method of introducing a Mo layer at the interface of a SiC / Ti3Al composite material of the present invention is intended to enhance the interface strength and reduce the interface residual stress. In view of the difference in thermal expansion coefficients between SiC and Ti3Al, interfacial thermal stress may be induced during the high-temperature forming stage, thereby posing a potential threat to the comprehensive performance of the composite material. Mo, by virtue of its unique physical properties, has a thermal expansion coefficient that is more matched with SiC and Ti3Al, and can achieve a smooth transition of the thermal expansion coefficient at the interface of the composite material. It can not only effectively disperse and relieve stress at the interface, but also significantly improve the interfacial bonding strength between SiC and Ti3Al, thereby ensuring that the composite material can maintain its performance stability when undergoing temperature changes.

[0041] After obtaining the SiC fiber with a deposited Mo interface layer, the present invention uses a Ti3Al alloy target and Nb as target materials, performs target magnetron sputtering on the SiC fiber with a deposited Mo interface layer under argon conditions, and alternately deposits Ti3Al layers and Nb layers on the surface of the SiC fiber with a deposited Mo interface layer to obtain a precursor wire with a multilayer structure.

[0042] In the present invention, the conditions for magnetron sputtering the target in step (3) include:

[0043] When depositing the Ti3Al layer, the argon gas flow rate is 40 to 100 sccm, and in a specific embodiment, it can be 50 sccm, 60 sccm or 80 sccm; the vacuum degree in the coating chamber is less than 4×10 -4 Pa, the gas pressure in the coating chamber is 0.7-1.2 Pa, and in a specific embodiment, it can be 0.8 Pa or 1.0 Pa; the sputtering bias is -40--150 V, and in a specific embodiment, it can be -80 V, -100 V or -130 V; the sputtering current is 1.6-2.4 A, and in a specific embodiment, it can be 1.8 A or 2.0 A; the power is 600-800 W, and in a specific embodiment, it can be 700 W or 750 W; the deposition rate is 2-4 μm / h, and in a specific embodiment, it can be 2.2 μm / h, 2.8 μm / h or 3.4 μm / h.

[0044] When depositing the Nb layer, the argon gas flow rate is 40 to 100 sccm, and in a specific embodiment, it can be 50 sccm, 60 sccm or 80 sccm; the vacuum degree in the coating chamber is less than 4×10 -4 Pa, the gas pressure in the coating chamber is 0.7-1.2Pa, and in a specific embodiment, it can be 0.8Pa or 1.0Pa; the sputtering bias is -40--150V, and in a specific embodiment, it can be -80V, -100V or -130V; the sputtering current is 0.8-1.2A, and in a specific embodiment, it can be 1.0A or 1.1A; the power is 300-500W, and in a specific embodiment, it can be 350W or 400W; the deposition rate is 0.4-1.5μm / h, and in a specific embodiment, it can be 0.6μm / h, 0.8μm / h or 1.2μm / h.

[0045] In the present invention, the rotation rate of the sample holder in step (1), step (2) and step (3) is 1 to 6 r / min, and in a specific embodiment, it can be 2 r / min, 4 r / min or 5 r / min.

[0046] In the present invention, in the step (3), one Ti3Al layer and one Nb layer are one period, and the repetition period of the Ti3Al layer and the Nb layer is ≥3, and in a specific embodiment, it can be 5, 6, 8 or 9; the thickness of a single Ti3Al layer is 2 to 6 μm, and in a specific embodiment, it can be 3 μm, 4 μm or 5 μm; the thickness of a single Nb layer is 0.5 to 4 μm, and in a specific embodiment, it can be 1 μm, 2 μm or 3 μm.

[0047] In the present invention, in the precursor yarn with a multi-layer structure, the total thickness of the SiC fiber surface film layer is 20 to 35 μm, and in a specific embodiment, it can be 25 μm, 28 μm, 30 μm or 32 μm.

[0048] After obtaining the precursor wire with a multi-layer structure, the present invention arranges the precursor wire with a multi-layer structure evenly and performs hot isostatic pressing to obtain the high-strength and low-stress continuous SiC fiber reinforced Ti3Al composite material.

[0049] The hot isostatic pressing process comprises the following steps:

[0050] The precursor wires with a multi-layer structure are tightly and evenly arranged and placed in a Ti3Al alloy sleeve for ion beam packaging to obtain a prefabricated sample; the prefabricated sample is hot isostatically pressed, and after the hot isostatic pressing is completed, the sample is cooled to room temperature with the furnace.

[0051] In the present invention, the SiC fibers are evenly arranged on the sample holder, and the distance between adjacent SiC fibers is 0.1-0.5 mm, and in a specific embodiment, it can be 0.2 mm or 0.3 mm.

[0052] In the present invention, the temperature of the hot isostatic pressing is 920-980°C, and in a specific embodiment, it can be 960 or 970°C; the pressure is 120-180MPa, and in a specific embodiment, it can be 130MPa, 150MPa or 160MPa; the time is 1-3h, and in a specific embodiment, it can be 2h or 2.5h.

[0053] The present invention also provides a high-strength and low-stress continuous SiC fiber reinforced Ti3Al composite material prepared by the preparation method described in the above technical scheme, which is obtained by hot isostatic pressing of a pioneer wire with a multi-layer structure, and is characterized in that a single pioneer wire with a multi-layer structure includes SiC fibers, carbon layers, Mo interface layers, and alternating Ti3Al layers and Nb layers from the inside to the outside, and the outermost layer of the pioneer wire with a multi-layer structure is a Nb layer.

[0054] The present invention also provides the application of the high-strength and low-stress continuous SiC fiber reinforced Ti3Al composite material described in the above technical solution as an aerospace material.

[0055] In order to further illustrate the present invention, the high-strength and low-stress continuous SiC fiber reinforced Ti3Al composite material provided by the present invention and its preparation method and application are described in detail below in combination with the accompanying drawings and embodiments, but they should not be understood as limiting the scope of protection of the present invention.

[0056] In the following embodiments, the continuous SiC fiber containing a carbon layer and the Ti3Al alloy target are provided by the Beijing Institute of Aeronautical Materials, and the Mo and Nb targets are commercially available; the diameter of the continuous SiC fiber containing a carbon layer is 90 to 110 μm; and the thickness of the carbon layer is 2 to 4 μm.

[0057] In the present invention, the high-strength and low-stress continuous SiC fiber reinforced Ti3Al composite material is denoted as SiC f / C / Mo / (Ti3Al / Nb)n, where SiC f refers to SiC fiber, and n represents the repetition period of alternately deposited Ti3Al layers and Nb layers.

[0058] Example 1

[0059] according to Figure 1 The flow chart shown in the figure is used to prepare high-strength and low-stress continuous SiC fiber reinforced Ti3Al composite materials. The specific steps are:

[0060] (1) Pretreatment: After the required target material and SiC fiber filaments are placed at the designated position in the coating chamber of the multi-target magnetron sputtering system, the vacuum degree in the coating chamber is lower than 4×10 -4 Pa, turn on the sample holder rotation switch, introduce argon gas, and control the pressure in the coating chamber at 0.8 Pa. Turn on the ion source power supply, then adjust the ion source voltage to 800V, clean for 30 minutes, turn off the ion source, and complete the cleaning;

[0061] (2) Mo interface layer construction: The vacuum degree in the coating chamber is less than 4×10 -4 Pa, adjust the argon flow rate, and control the gas pressure in the coating chamber to 0.8 Pa. Turn on the bias power supply and set it to -100V. Turn on the DC power supply of the Mo target to sputter the target, with a sputtering current of 1A, a power of 400W, and a deposition rate of 1μm / h, and a 2μm Mo layer is deposited on the surface of the SiC fiber;

[0062] (3) Multilayer construction of Ti3Al+Nb matrix: Adjust the argon flow rate to control the gas pressure in the coating chamber at 0.8 Pa. Turn on the bias power supply and set it to -100V. At the same time, turn on the DC power supply of the Ti3Al alloy target and the Nb metal target to sputter the targets. During the deposition of the Ti3Al layer, the sputtering current is 2A, the power is 700W, and the deposition rate is 4μm / h; during the deposition of the Nb layer, the sputtering current is 1A, the power is 400W, and the deposition rate is 1μm / h. By controlling the sample holder speed to 3r / min, a 2μm thick Ti3Al layer and a 0.5μm thick Nb layer are alternately deposited on the surface of the SiC fiber. Ti3Al layer + Nb layer is one cycle. Repeat the deposition for 9 cycles to obtain a precursor wire with a multilayer structure.

[0063] The precursor wires were arranged tightly and evenly, placed in a Ti3Al alloy sleeve, and then ion beam packaged. The prefabricated sample was hot isostatically pressed at 960°C and 180 MPa for 3 h. After the hot isostatic pressing was completed, the sample was cooled to room temperature with the furnace to obtain SiC f / C / Mo / (Ti3Al / Nb)9 composite materials.

[0064] Example 2

[0065] (1) Pretreatment: After the required target material and SiC fiber filaments are placed at the designated position in the coating chamber of the multi-target magnetron sputtering system, the vacuum degree in the coating chamber is lower than 4×10 -4 Pa, turn on the sample holder rotation switch, introduce argon gas, and control the pressure in the coating chamber at 0.8 Pa. Turn on the ion source power supply, then adjust the ion source voltage to 800V, clean for 30 minutes, turn off the ion source, and complete the cleaning;

[0066] (2) Mo interface layer construction: The vacuum degree in the coating chamber is less than 4×10 -4 Pa, adjust the argon flow rate, and control the gas pressure in the coating chamber to 0.8 Pa. Turn on the bias power supply and set it to -100V. Turn on the DC power supply of the Mo target to sputter the target, with a sputtering current of 1A, a power of 400W, and a deposition rate of 1μm / h, and a 2μm Mo layer is deposited on the surface of the SiC fiber;

[0067] (3) Multilayer construction of Ti3Al+Nb matrix: Adjust the argon flow rate to control the gas pressure in the coating chamber at 0.8 Pa. Turn on the bias power supply and set it to -100V. At the same time, turn on the DC power supply of the Ti3Al alloy target and the Nb metal target to sputter the targets. During the deposition of the Ti3Al layer, the sputtering current is 2A, the power is 700W, and the deposition rate is 4μm / h; during the deposition of the Nb layer, the sputtering current is 1A, the power is 400W, and the deposition rate is 1μm / h. By controlling the sample holder speed to 3r / min, a 4μm thick Ti3Al layer and a 0.5μm thick Nb layer are alternately deposited on the surface of the SiC fiber. The Ti3Al layer + Nb layer is one cycle. Repeat the deposition for 5 cycles to obtain a precursor wire with a multilayer structure.

[0068] The precursor wires were arranged tightly and evenly, placed in a Ti3Al alloy sleeve, and then ion beam packaged. The prefabricated sample was hot isostatically pressed at 960°C and 180 MPa for 3 h. After the hot isostatic pressing was completed, the sample was cooled to room temperature with the furnace to obtain SiC f / C / Mo / (Ti3Al / Nb)5 composite materials.

[0069] Example 3

[0070] (1) Pretreatment: After the required target material and SiC fiber filaments are placed at the designated position in the coating chamber of the multi-target magnetron sputtering system, the vacuum degree in the coating chamber is lower than 4×10 -4 Pa, turn on the sample holder rotation switch, introduce argon gas, and control the pressure in the coating chamber at 0.8 Pa. Turn on the ion source power supply, then adjust the ion source voltage to 800V, clean for 30 minutes, turn off the ion source, and complete the cleaning;

[0071] (2) Mo interface layer construction: The vacuum degree in the coating chamber is less than 4×10 -4 Pa, adjust the argon flow rate, and control the gas pressure in the coating chamber to 0.8 Pa. Turn on the bias power supply and set it to -100V. Turn on the DC power supply of the Mo target to sputter the target, with a sputtering current of 1A, a power of 400W, and a deposition rate of 1μm / h, and a 2μm Mo layer is deposited on the surface of the SiC fiber;

[0072] (3) Multilayer construction of Ti3Al+Nb matrix: Adjust the argon flow rate to control the gas pressure in the coating chamber at 0.8 Pa. Turn on the bias power supply and set it to -100V. At the same time, turn on the DC power supply of the Ti3Al alloy target and the Nb metal target to sputter the targets. During the deposition of the Ti3Al layer, the sputtering current is 2A, the power is 700W, and the deposition rate is 4μm / h; during the deposition of the Nb layer, the sputtering current is 1A, the power is 400W, and the deposition rate is 1μm / h. By controlling the sample holder speed to 3r / min, a 6μm thick Ti3Al layer and a 0.5μm thick Nb layer are alternately deposited on the surface of the SiC fiber. The Ti3Al layer + Nb layer is one cycle. Repeat the deposition for 3 cycles to obtain a precursor wire with a multilayer structure.

[0073] The precursor wires were arranged tightly and evenly, placed in a Ti3Al alloy sleeve, and then ion beam packaged. The prefabricated sample was hot isostatically pressed at 960°C and 180 MPa for 3 h. After the hot isostatic pressing was completed, the sample was cooled to room temperature with the furnace to obtain SiC f / C / Mo / (Ti3Al / Nb)3 composite material.

[0074] Comparative Example 1

[0075] (1) Pretreatment: After the required target material and SiC fiber filaments are placed at the designated position in the coating chamber of the multi-target magnetron sputtering system, the vacuum degree in the coating chamber is lower than 4×10 -4 Pa, turn on the sample holder rotation switch, introduce argon gas, and control the pressure in the coating chamber at 0.8 Pa. Turn on the ion source power supply, then adjust the ion source voltage to 800V, clean for 30 minutes, turn off the ion source, and complete the cleaning;

[0076] The vacuum degree in the coating chamber is less than 4×10 -4Pa, adjust the argon flow rate, and control the gas pressure in the coating chamber to 0.8 Pa. Turn on the bias power supply and set it to -100V. Turn on the DC power supply of the Ti3Al target to sputter the target. The sputtering current is 2A, the power is 700W, and the deposition rate is 4μm / h. A 22μm Ti3Al layer is deposited on the surface of the SiC fiber to obtain a SiC / C / Ti3Al precursor wire;

[0077] The SiC / C / Ti3Al precursor wires were arranged tightly and evenly, placed in a Ti3Al alloy sleeve, and then ion beam packaged. The obtained prefabricated sample was hot isostatically pressed at 960°C and 180 MPa for 3 h. After the hot isostatic pressing was completed, the sample was cooled to room temperature with the furnace to obtain SiC f / C / Ti3Al composite materials.

[0078] Comparative Example 2

[0079] After the required target material and SiC fiber are placed at the designated position in the coating chamber of the multi-target magnetron sputtering system, the vacuum degree in the coating chamber is lower than 4×10 -4 Pa, turn on the sample holder rotation switch, introduce argon gas, and control the pressure in the coating chamber at 0.8 Pa. Turn on the ion source power supply, then adjust the ion source voltage to 800V, clean for 30 minutes, turn off the ion source, and complete the cleaning;

[0080] The vacuum degree in the coating chamber is less than 4×10 -4 Pa, adjust the argon flow rate, and control the gas pressure in the coating chamber to 0.8 Pa. Turn on the bias power supply and set it to -100V. Turn on the DC power supply of the Mo target to sputter the target, with a sputtering current of 1A, a power of 400W, and a deposition rate of 1μm / h, and a 2μm Mo layer is deposited on the surface of the SiC fiber;

[0081] Adjust the argon flow rate to control the gas pressure in the coating chamber at 0.8 Pa. Turn on the bias power supply and set it to -100V. Turn on the DC power supply of the Ti3Al alloy target to sputter the target. The sputtering current is 2A, the power is 700W, and the deposition rate is 4μm / h. A 22μm thick Ti3Al layer is deposited on the surface of the Mo layer to obtain a SiC / C / Mo / Ti3Al precursor wire.

[0082] The SiC / C / Mo / Ti3Al precursor wires were arranged tightly and evenly, placed in a Ti3Al alloy sleeve, and then ion beam packaged. The obtained prefabricated sample was hot isostatically pressed at 960°C and 180 MPa for 3 h. After the hot isostatic pressing was completed, the sample was cooled to room temperature with the furnace to obtain SiC f / C / Mo / Ti3Al composite materials.

[0083] Test Case

[0084] Figure 2 The SiC obtained in Example 1 f Cross-sectional SEM of / C / Mo / (Ti3Al / Nb)9 composite material, Figure 2 (a) and (b) are cross-sectional SEM images at scales of 100 μm and 30 μm, respectively. Figure 2 The results show that the SiC prepared by the present invention f / C / Mo / (Ti3Al / Nb)9 composite material has a multilayer structure.

[0085] According to GB / T 228.2-2015 and GB / T 228.1-2021, the high temperature tensile strength and room temperature tensile strength are tested respectively. Figure 3 is a comparison chart of the tensile strength of the composite materials obtained in Example 1 and Comparative Examples 1-2. Figure 3 It can be seen that the SiC prepared by the present invention f Compared with the SiC / C / Mo / (Ti3Al / Nb)9 composite without matrix multilayer structure, f / C / Mo / Ti3Al composites and SiC without Mo interface layer f / C / Ti3Al composite materials have significantly improved tensile strength both at room temperature and at high temperature.

[0086] Figure 4 is a comparison diagram of the residual stress of the composite materials obtained in Example 1 and Comparative Examples 1-2. Figure 4 It can be seen that the SiC prepared by the present invention f Compared with the SiC / C / Mo / (Ti3Al / Nb)9 composite without matrix multilayer structure, f / C / Mo / Ti3Al composites and SiC without Mo interface layer f / C / Ti3Al composite material, the residual stress inside the composite material is significantly reduced, indicating that the interface layer and the matrix multilayer designed in the present invention can effectively alleviate or release the residual stress at the interface of the composite material and in the matrix, thereby improving the performance of the SiC / Ti3Al composite material.

[0087] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. People can also obtain other embodiments based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.

Claims

1. A method for preparing a high-strength and low-stress continuous SiC fiber reinforced Ti3Al composite material, characterized in that: The following steps are involved: (1) ion cleaning the SiC fiber containing the carbon layer under argon conditions to obtain a pretreated SiC fiber; (2) using Mo as a target material, magnetron sputtering the pretreated SiC fiber under argon conditions to obtain a SiC fiber with a Mo interface layer deposited thereon; (3) using a Ti3Al alloy target and Nb as target materials, magnetron sputtering the SiC fiber deposited with the Mo interface layer under argon conditions, and alternately depositing Ti3Al layers and Nb layers on the surface of the SiC fiber deposited with the Mo interface layer to obtain a precursor wire with a multilayer structure; The precursor wires with a multi-layer structure are evenly arranged and hot isostatically pressed to obtain the high-strength and low-stress continuous SiC fiber reinforced Ti3Al composite material.

2. The preparation method according to claim 1, characterized in that: The ion cleaning is carried out in the coating chamber of the magnetron sputtering system, and the vacuum degree in the coating chamber is less than 4×10 -4 Pa; the gas flow value of argon is 40-80 sccm, the ion source voltage is 750-850 V, and the cleaning time is 20-30 min.

3. The preparation method according to claim 1, characterized in that: The conditions for magnetron sputtering in step (2) include: an argon gas flow rate of 40 to 100 sccm; a vacuum degree in the coating chamber of less than 4×10 -4 Pa, the gas pressure in the coating chamber is 0.7~1.2Pa; the sputtering bias is -40~-150V, the sputtering current is 0.8~1.2A, the power is 300~500W, and the deposition rate is 0.4~1.5μm / h.

4. The preparation method according to claim 1, characterized in that: The conditions for magnetron sputtering the target in step (3) include: When depositing the Ti3Al layer, the argon flow rate is 40-100 sccm and the vacuum degree in the coating chamber is less than 4×10 -4 Pa, the gas pressure in the coating chamber is 0.7~1.2Pa, the sputtering bias is -40~-150V, the sputtering current is 1.6~2.4A, the power is 600~800W, and the deposition rate is 2~4μm / h; When depositing the Nb layer, the argon flow rate is 40-100 sccm and the vacuum degree in the coating chamber is less than 4×10 -4 Pa, the gas pressure in the coating chamber is 0.7~1.2Pa, the sputtering bias is -40~-150V, the sputtering current is 0.8~1.2A, the power is 300~500W, and the deposition rate is 0.4~1.5μm / h.

5. The preparation method according to claim 1, characterized in that: The SiC fiber is a SiC fiber containing a tungsten core; the diameter of the SiC fiber is 90 to 110 μm, and the thickness of the carbon layer is 2 to 4 μm; The thickness of the Mo interface layer is 0.5-4 μm.

6. The preparation method according to claim 1, characterized in that: In the step (3), one Ti3Al layer and one Nb layer constitute one cycle, and the repetition period of the Ti3Al layer and the Nb layer is ≥3; The thickness of the single Ti3Al layer is 2 to 6 μm, and the thickness of the single Nb layer is 0.5 to 4 μm.

7. The preparation method according to claim 1, characterized in that: In the precursor yarn with a multi-layer structure, the total thickness of the SiC fiber surface film layer is 20 to 35 μm.

8. The preparation method according to claim 1, characterized in that: The temperature of the hot isostatic pressing is 920-980° C., the pressure is 120-180 MPa, and the time is 1-3 hours.

9. The high-strength and low-stress continuous SiC fiber reinforced Ti3Al composite material prepared by the preparation method according to any one of claims 1 to 8 is obtained by hot isostatic pressing of precursor wires with a multilayer structure, characterized in that: A single precursor wire with a multi-layer structure includes SiC fiber, a carbon layer, a Mo interface layer, and alternating Ti3Al layers and Nb layers from the inside to the outside, and the outermost layer of the precursor wire with a multi-layer structure is a Nb layer.

10. Use of the high-strength and low-stress continuous SiC fiber reinforced Ti3Al composite material according to claim 9 as an aerospace material.

Citation Information

Patent Citations

  • Anti-cracking preparation method of TiAl-based composite material

    CN115074686A

  • High-toughness fiber-reinforced TiAl / Ti3Al multilayer composite material as well as preparation method and application thereof

    CN118422142A

  • Production of silicon carbide fiber reinforced titanium-aluminum composite material

    JP1997041053A

  • Long fiber reinforced ceramic composite material having self-healing capacity

    JP2012148963A

  • Boron carbide fiber reinforced articles

    US20160122252A1

Cited By

  • Continuous SiC fiber reinforced titanium-aluminum matrix composite fastener with high temperature resistance and low thermal expansion effect and preparation method of continuous SiC fiber reinforced titanium-aluminum matrix composite fastener

    CN121826559A

  • Optimization design method for continuous SiC fiber reinforced titanium-aluminum matrix composite fastener based on finite element method

    CN121980850A